Critical Analysis Of Tuberous Sclerosis In A Family - Raghu Tanjore Y; Kanthraj Garehatty R (Wolters Kluwer Medknow Publications, 2000)
Tuberous sclerosis (TS) is an autosomal neurocutaneous genodermatosis. Sporadic cases have been reported. We report three cases of TS in a family. A 30 year male labourer and his two off springs, 10 years male and 8 year female, born of no consanguineous marriage, presented with facial angiofibroma, ash leaf macule, shagreen patch, periungual fibroma, mental deficiency, delayed milestone and epilepsy. Plain and contrast computerized tomography revealed subependymal calcification on the body of both lateral ventricles in the female child.